PEMBUATAN APLIKASI STEGANOGRAFI PADA CITRA DIGITAL - Dian Gustina; Achmad Sumbaryadi (JSI (Jurnal Sistem Informasi) Universitas Suryadarma, 2016)
Steganografi has the function to hide information in the form of digital text data. Medium used is a digital image. The secret message in paste in the picture here is done by using a technique that Steganografi only limited to JPEG images. Steganografi as an art and science for the concealment of information or messages in other messages to cover other media such as images, audio MP3, so as not to arouse suspicion. Steganografi techniques can be used to hide data in digital with little or no change was visible in the image and can be exploited to export the secret message. Discussion related to the authors are interested in creating applications steganografi, which aims to hide the message so discreet. To accommodate a secret message into a digital object that is in the form of a digital image certainly requires an algorithm that can modify the digital object to produce a new digital object that contains a hidden message, which is called the embedding algorithm